2014
DOI: 10.3102/0002831213508299
|View full text |Cite
|
Sign up to set email alerts
|

The Random Assignment of Students Into Elementary Classrooms

Abstract: Value-added models (VAMs) are used to measure changes in student achievement on large-scaled standardized test scores from year to year. When aggregated, VAM estimates are used to measure teacher effectiveness and hold teachers accountable for the value they purportedly add to or detract from student learning and achievement. In this study, researchers examined the extent to which purposeful (nonrandom) and random assignment of students into classrooms occurs in Arizona elementary schools (Grades 3–6). Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…A recent study by Paufler and Amrein-Beardsley (2014) provides insight into what those student assignment mechanisms might be. The authors surveyed over 300 elementary school principals in Arizona, 98% of whom reported using student and teacher information during the placement process in an effort to match learning and teaching styles, personalities, and special needs with the objective of maximizing student outcomes.…”
Section: Implications To Practices For Reducing Summer Biasesmentioning
confidence: 99%
“…A recent study by Paufler and Amrein-Beardsley (2014) provides insight into what those student assignment mechanisms might be. The authors surveyed over 300 elementary school principals in Arizona, 98% of whom reported using student and teacher information during the placement process in an effort to match learning and teaching styles, personalities, and special needs with the objective of maximizing student outcomes.…”
Section: Implications To Practices For Reducing Summer Biasesmentioning
confidence: 99%
“…The placement of students into teachers’ classrooms occurs more or less at random, so really any effects that might be observed among teachers might be reasonably attributed to students’ teachers provided advanced statistical tools and techniques are used. The assignment of students to classrooms (and teachers to classrooms, as well as students and teachers to schools) is much farther from random than is often assumed, and this biases VAM estimates and weakens arguments that teachers, not students, were responsible for the effects observed (see, for example, Bausell, 2013; Braun, 2005; Paufler & Amrein-Beardsley, 2014; Rothstein, 2009, 2010, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This is appropriate for some universities and some selective primary and secondary schools (e.g., if using ACT scores both for admissions and as a covariate in the model). It is also applicable for teacher evaluation within schools where students may be streamed into a class based on previous performance (Paufler & Amrein-Beardsley, 2014). This is important because sometimes these methods are used to estimate teacher effectiveness (Amrein-Beardsley, 2014).…”
Section: Simulation Methodsmentioning
confidence: 99%